Role of absorptive capacity in predicting continuance intention to use digital libraries: An empirical study - Hossain M.E.; Bhuiyan T.; Mahmud I.; Ramayah T.; Scholtz B. (Springer Verlag, 2024)
The purpose of this paper is to investigate the impact of absorptive capacity and the quality dimensions of technology on students continuance intention to use the e-library system. To measure the continuance intention, an integrated research model was developed using expectation-confirmation theory (ECT) and absorptive capacity theory. This empirical study was undertaken at a university in Bangladesh with a sample size of 297. Data was collected via a survey questionnaire. The results reveal that the dimensions of absorptive capacity have a strong effect on confirmation of the system and a partial impact on perceived usefulness (PU). Confirmation of the system has a significant effect on the PU of and satisfaction with the system. Satisfaction was found to be a strong predictor for the continuance intention to use the e-library. Finally, ECT fully fits in this context and students satisfaction has the largest effect on the continuance intention. ICST Institute for Computer Sciences, Social Informatics and Telecommunications Engineering 2018.